What is stalking?: the match between legislation and public perception - Sheridan, Lorraine (Legal and criminological psychology, 2001)
Purpose. To assess the match between anti-stalking legislation and participants' own opinions of what constitutes stalking, and to test the ability of lay persons to interpret anti-stalking statutes. Method. University students (N= 88) were presented with 20 transcripts of actual intrusive acts, as experienced by female members of the public. Participants were asked to rate the extent to which each represented a case of stalking, either on the basis of one of three sets of anti-stalking legislation, or purely on the basis of their own opinions as to what constituted stalking. Results. Multivariate and univariate analyses of variance revealed that the three laws, and participants' own opinions, led to significant differences in whether a given transcript was labelled as stalking for 18 of the 20 transcripts. This reflected the way in which the different legislation chose to define stalking. Participants' intuitive ideas fitted most closely with ratings generated by the England and Wales Protection from Harassment Act 1997. Conclusions. Although problems of defining stalking in relation to public perception persist, the England and Wales Protection from Harassment Act 1997, which offers no final definition of stalking but concentrates upon the effects on the victim, may come closest to capturing the public perception of the crime. It was also concluded that lay persons were proficient in interpreting and applying three anti-stalking laws of varying complexity.